IL-12 Augments Antitumor Responses to Cycled Chemotherapy. Issue 4 (May 2015) - Zhang, Lingbing; Feng, Dongdong; Hu, Yingbin; Tsung, Kangla; Norton, Jeffrey A.
Abstract : Loss of antitumor response to repeated chemotherapy is a major cause of treatment failure in cancer patients. The development of acquired drug resistance is thought to come primarily from changes in tumor cells, and not host response to the tumor. Our recent study shows that antitumor immunity is activated and contributes significantly to the efficacy of chemotherapy. In this study of mouse tumor models, we demonstrate that loss of antitumor response during multiple cycles of chemotherapy is associated with a lack of immune activation, and not intrinsic tumor cell drug resistance. More importantly, we show that adding interleukin-12 (IL-12) to cycled chemotherapy maintains and even increases antitumor immune response in both immunogenic and nonimmunogenic murine tumors and significantly prolongs survival. In some instances, larger tumor burdens that relapse following an initial cycle of cyclophosphamide and IL-12 are eradicated by subsequent cycles of the same treatment at the same doses. Further analysis demonstrates that the initial cycle of the combined therapy increases antitumor immunity of the host. In other mice when tumors are not eradicated by the current cycle of therapy, it serves as a starting point for the subsequent cycles of treatment to generate higher levels of antitumor immunity and greater antitumor response. These results show that the status of host antitumor immunity is a critical factor affecting antitumor efficacy during repeated administration of chemotherapy. Further, IL-12 augments the antitumor immune response under such conditions. Abstract : Supplemental Digital Content is available in the text.